Factors Influencing the Attractiveness of Tourism Destination (Case Study: Siti Nurbaya/Gunung Padang Park Area in Padang City) - Windy Della Sari; Siti Permata Pricilla; Rifdatul Husna (Jurnal Multidisiplin Sahombu, 2025)
This research is a quantitative descriptive study with a descriptive-correlational approach, examining the extent to which core resources and attractors as well as supporting factors influence the attractiveness of tourism in the Siti Nurbaya/Gunung Padang Park Area to date. Data were collected through a Likert-scale questionnaire distributed to 100 tourists, selected using a non-probability sampling technique. Data analysis was conducted using SPSS, including descriptive analysis, Pearson correlation, and multiple regression. The results show that the variables of culture and history, mix of activity, and infrastructure have a significant influence on tourism attractiveness, accounting for 51%, while other variables such as superstructure, marketing, and accessibility do not have a significant effect. These findings indicate that cultural-historical preservation, the provision of diverse tourism activities, and infrastructure improvement are key factors in enhancing the attractiveness of the Siti Nurbaya/Gunung Padang Park Area.